Daya Tahan Coldmix Asphalt Sebagai Bahan Darurat Penanganan Jalan dengan Bahan Resin Fiberglass Sebagai Pengganti Aspal - Maulana, Achmad Hanif; Damara, Bobby (Universitas Batanghari Jambi, 2024)
Asphalt is a material that is widely used in road construction. The use of asphalt materials is getting higher, but the asphalt materials used are increasingly expensive and limited, research was conducted with Coldmix Ashpalt with the addition of fiberglass resin with the aim of determining the effect of adding fiberglass resin to AC-WC asphalt materials. The method used for research is carried out in the laboratory with the marshall test method then obtained the calculation results, namely the marshall quotient. The characteristics of AC-WC pavement mixtures include density, cavities in aggregate minerals (VMA), asphalt filled cavities (VFA), voids in the mixture (VIM), stability, marshall melt (flow), and Marshall Quotient (MQ). The results of the study of 4 variations of the deep fiberglass resin mixture used with variation values of 0%, 2%, 3%, 4%. for the variation value that has the highest stability is found in the 3% variation with a stability value of 1577.33 kg, with a VMA value of 15.50%, VFA value of 87.18%, VIM value of 3.28%, flow value of 3.13 mm, and MQ value of 510.72 kg / mm. The variation content of 3% is declared the most effective for mixing AC-WC asphalt because the values of the marshall properties meet the 2018 Highways engineering specifications, so that the most optimal variation of fiberglass resin added material is used as a mixture of AC-WC asphalt with a penetration of 60/70.